2015
DOI: 10.1039/c4dt03143a
|View full text |Cite
|
Sign up to set email alerts
|

UV-visible spectroscopy of macrocyclic alkyl, nitrosyl and halide complexes of cobalt and rhodium. Experiment and calculation

Abstract: Transition metal complexes (NH3)5CoX(2+) (X = CH3, Cl) and L(H2O)MX(2+), where M = Rh or Co, X = CH3, NO, or Cl, and L is a macrocyclic N4 ligand are examined by both experiment and computation to better understand their electronic spectra and associated photochemistry. Specifically, irradiation into weak visible bands of nitrosyl and alkyl complexes (NH3)5CoCH3(2+) and L(H2O)M(III)X(2+) (X = CH3 or NO) leads to photohomolysis that generates the divalent metal complex and ˙CH3 or ˙NO, respectively. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In developing a Slater determinant based direct CI approach, Ruedenberg and Ivanic 51,52 found that approximately 50% of configurations in CISD were non-significant contributors to the energy. The picture was worse for CISDT and CISDTQ with some 90% of configurations being non-significant deadwood 52 .…”
Section: Ormasmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing a Slater determinant based direct CI approach, Ruedenberg and Ivanic 51,52 found that approximately 50% of configurations in CISD were non-significant contributors to the energy. The picture was worse for CISDT and CISDTQ with some 90% of configurations being non-significant deadwood 52 .…”
Section: Ormasmentioning
confidence: 99%
“…and CISDTQ (including quadruples excitations) 98% for most systems 26,51,52 . While CI methods are introduced in computational chemistry textbooks previously referenced, the review article by Sherrill and Shaefer 26 is invaluable for gaining a good understanding of the method.…”
Section: Configuration Interaction (Ci)mentioning
confidence: 99%
“…TDDFT calculations 51 on this system indicated that this photochemistry is mostly due to interactions between TDDFT natural orbitals 100 and 101. Those TDDFT calculations were previously performed 51 with GAMESS 19,20 and NWCHEM 52 using the Stuttgart small core ECP 31,32,53 for the rhodium, and the cc-pVDZ 23 basis set for the remaining atoms. Currently VVO calculations require all-electron basis sets, so for the VVO calculation, the all electron Sapporo [54][55][56] augmented double zeta basis sets were chosen for computational efficiency.…”
Section: Transition Metalsmentioning
confidence: 99%